2017
DOI: 10.1371/journal.pone.0178668
|View full text |Cite
|
Sign up to set email alerts
|

Local cryotherapy improves adjuvant-induced arthritis through down-regulation of IL-6 / IL-17 pathway but independently of TNFα

Abstract: ObjectivesLocal cryotherapy is widely and empirically used in the adjuvant setting in rheumatoid arthritis treatment, however its own therapeutic and anti-inflammatory effects are poorly characterized. We aimed to evaluate the effects of local cryotherapy on local and systemic inflammation in Adjuvant-induced arthritis, a murine model of rheumatoid arthritis.MethodsThe effects of mild hypothermia (30°C for 2 hours) on cytokine protein levels (Multiplex/ELISA) were evaluated in vitro in cultured rat adjuvant-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 53 publications
(70 reference statements)
3
17
0
1
Order By: Relevance
“…These observations were partly confirmed by Guillot et al [22] in rats with adjuvant-induced arthritis exposed to local cryotherapy. These authors showed that the treatment with ice was better tolerated and had beneficial effects on arthritis score and joint swelling, while cold gas application induced transient arthritis worsening.…”
Section: Discussionsupporting
confidence: 63%
“…These observations were partly confirmed by Guillot et al [22] in rats with adjuvant-induced arthritis exposed to local cryotherapy. These authors showed that the treatment with ice was better tolerated and had beneficial effects on arthritis score and joint swelling, while cold gas application induced transient arthritis worsening.…”
Section: Discussionsupporting
confidence: 63%
“…Our study provides a new scientific contribution on the benefits of clinical-like cryotherapy in the treatment of acute knee arthritis in an animal model. It is also used empirically as a complementary treatment for rheumatoid arthritis, with a good tolerance profile when compared to corticosteroids or non-steroidal anti-inflammatory drugs (NSAIDs); however, the protocols have not been standardized (7).…”
Section: Discussionmentioning
confidence: 99%
“…Studying the possible effects of cryotherapy in an arthritis model may be useful for clinical practice. The ice pack was considered a welltolerated modality of therapy (7), and it was effective to ameliorate joint and muscle damage in chronic models of transection of the anterior cruciate ligament (8).…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic hypothermia shows normalizing effect on metabolic processes disturbed in ischaemic conditions, including improving metabolism and maintaining glucose balance in the brain, lowering the concentration of lactates formed as a result of anaerobic metabolism, reducing the intensity of cellular acidosis, limiting the secretion of free radicals in damaged neurons, lowering the production of pro-inflammatory cytokines (TNF-α, IL-6), stabilizes the blood-brain barrier and reduces endothelial dysfunction preventing ischaemic damage to tissues and organs [14][15][16][17][18].…”
Section: Effect Of Hypothermia On the Human Bodymentioning
confidence: 99%